2013
DOI: 10.1007/s40279-013-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Achilles and Patellar Tendinopathy Loading Programmes

Abstract: There is little clinical or mechanistic evidence for isolating the eccentric component, although it should be made clear that there is a paucity of good quality evidence and several potential mechanisms have not been investigated, such as neural adaptation and central nervous system changes (e.g. cortical reorganization). Clinicians should consider eccentric-concentric loading alongside or instead of eccentric loading in Achilles and patellar tendinopathy. Good-quality studies comparing loading programmes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 315 publications
(164 citation statements)
references
References 93 publications
2
136
0
5
Order By: Relevance
“…This was in agreement with our review. More recently, Malliaras et al 52 examined tendinopathy loading programmes with focus on mechanistic outcomes (such as torque measures) and did not examine patient report measures.…”
Section: Discussionmentioning
confidence: 99%
“…This was in agreement with our review. More recently, Malliaras et al 52 examined tendinopathy loading programmes with focus on mechanistic outcomes (such as torque measures) and did not examine patient report measures.…”
Section: Discussionmentioning
confidence: 99%
“…There was no clearly superior exercise programme. We found only limited evidence from one study in the Achilles tendon, and conflicting evidence in the patellar tendon, which showed that isolating eccentric muscle contraction is superior to other loading 1. Further, there was equivalent evidence for Silbernagel combined (Achilles) and greater evidence for HSR loading (patellar) 1.…”
Section: So What Is the Best Exercise Programme For Achilles And Patementioning
confidence: 67%
“…In 2013, our group published a systematic review of Achilles and patellar tendinopathy rehabilitation programmes 1. Eccentric loading involving slow lengthening muscle contractions was, and among many still is, regarded as the first choice rehabilitation option for these lower limb overuse conditions.…”
mentioning
confidence: 99%
“…However, Rathleff et al (2014) was the only study that examined a symptomatic population. It was also of particular significance given that high-load strength training that causes high tensile loads across the tendon has shown promising results on degenerative tendon disorders such as achilles and patellar tendinopathy (Cook & Purdam, 2009;Malliaras et al, 2013).…”
Section: Discussionmentioning
confidence: 99%